The Relationship between the Quality of Nursing Work Life and the Quality of Care for Patients in Inpatients Ward at Regional Hospitals in Jember Regency - Anisah Ardiana; Retno Purwandari; Mariatul Rochmawati Nuris Wahyuni (University of Muhammadiyah Malang, 2020)
The quality of care can be influenced by the quality of nurses' work-life which describes the satisfaction of nurses at the workplace. Therefore, this study was aimed to analyze the relationship between the quality of nurses' work-life and the quality of care for patients in the inpatient ward at regional hospitals in Jember Regency. A cross-sectional approach used among 53 nurses as a total sampling and 53 clients in the inpatient ward were chosen by purposive sampling. Data collection was done by filling out questionnaires on the quality of nurses' work-life and the quality of care for clients. The findings showed that the quality of nurses' work-life was good (49%) and the quality of care was good (49%). The analysis result by using Chi-square showed that there was a relationship between the quality of nurses' work-life and quality of care (p value=0.009,a=0.05). Research has found that poor nursing care quality is caused by the low quality of work-life. Nurses who had a good quality of nursing work-life would give good quality of care and otherwise. Therefore, planning strategies to create comfort workplace with improving each dimension of the quality of nurses' work-life is important to improve the quality of care.